Optimal Design of Fractional Order PID Controllers for Solid Oxide Fuel Cell System Employing PSO Algorithm - Singh, Swati; Tayal, Vijay Kuma; Singh, Hemender Pa; Yadav , Vinod Kumar (AIUB Journal of Science and Engineering (AJSE), 2022)
Solid Oxide Fuel Cells (SOFCs) are gaining attraction in order to facilitate various applications owing to portability, low pollution and high efficiency. However, due to strong nonlinearity, fast variations in loading conditions and sluggish dynamics, regulation of the output voltage of SOFCs is disturbed. This paper aims to enhance the dynamic performance of SOFC by employing PI, PI Fast, PIDF, 2-DOF PID and PSO optimized FO-PID controllers under uncertain input conditions. The PID tuner is used for tuning the PI, PI fast, PIDF and 2-DOF PID controller parameters. The PSO technique is utilized for optimizing of FO-PID controller. The SOFC output with various controllers is compared in terms of performance specifications such as peak overshoot, settling time, steady state error and rise time. The comparison of computer simulation results manifests that the proposed PSO-FOPID controller scheme yields in far better performance with SOFC subjected to uncertain input. Index Terms—FOPID-Fractional Order PID,